Prospective evaluation of echocardiographic parameters and cardiac biomarkers in healthy dogs eating four custom-formulated diets - Leach, Stacey B.; Clark, Stephanie D.; Baumwart, Ryan D.; McCauley, Sydney R.; Thomason, Justin D.; Streeter, Renee M.; Zumbaugh, Charles A.; Lamb, Ken; Quest, Bradley W. (Frontiers in Animal Science, 2023)
Introduction: Diet-associated dilated cardiomyopathy (DCM) has been suspected in breeds that have not been previously noted to have a pre-disposition to DCM phenotype. The study hypothesized that over the study’s duration, dogs fed diets varying in the amount of animal-source protein and carbohydrate sources would not have a negative impact on cardiac parameters and function. Methods: Thirty-two purebred beagles and 33 mixed-breed hounds were randomized into four diet groups and studied for 210 days. Diets fed were high animal protein grain-free (HAGF), low animal protein grain-free (LAGF), high animal protein grain-inclusive (HAGI), and low animal protein grain-inclusive (LAGI). Cardiac-specific biomarkers, endomyocardial biopsies, and linear and volumetric echocardiographic parameters were evaluated. Results: There was a treatment-by-day-by-breed effect for normalized left ventricular internal diameter at end-diastole (P = 0.0387) and normalized left ventricular internal diameter at end-systole (P = 0.0178). Mixed-breed hounds fed diet LAGI had a lower normalized left ventricular internal diameter at end-diastole compared to day 90. On day 210, beagles fed diet LAGF had a higher normalized left ventricular internal diameter at end-systole than beagles fed diet LAGI. Fractional shortening for beagles in LAGF was significantly lower (P = 0.007) than for beagles in HAGI and LAGI. Cardiac-specific biomarkers and endomyocardial biopsies were not significantly different for breeds, diets, and various time points. Discussion: This study did not detect the development of cardiac dysfunction throughout the duration of the study with the echocardiographic parameters measured, select cardiac biomarkers, or endomyocardial biopsies. There were noted interactions of treatment, breed, and time, therefore, isolating a diet association cannot be determined. Future research should further examine other factors that may help to identify the variable/s and possible mechanisms behind a suspected diet-associated DCM in dogs.